The effect of Shen’an pills on serum parameters associated with tissue fibrosis in patients with chronic kidney failure - HAN Yi-tong; SUN Yi-jun; YANG Huan-rong (Linchuang shenzangbing zazhi)
Objective To explore the therapeutic effect of Shen’an pills on renal fibrosis in patients with chronic kidney failure.Methods Those patients diagnosed with chronic kidney failure phase 3-5 by the department of nephrology in Weifang Yidu Centre Hospital from June 2016 to June 2017 were chosen to divide into the treatment group（n=42） and the control group（n=50）.All the patients were recommended to take some food with low content of valuable protein(0.6 g·kg-1·d-1) and low content of phosphorus,and to conduct symptomatic treatment with phosphate binders and hypotensive（if serum creatinine <265 μmol/L,ACEI or ARB was added）.At the same time,the patients in the treatment group took Shen’an pills regularly.All the patient in both the two group were observed for 6 months.Changes of the kidney function,inflammatory indicator and renal fibrosis indicator before treatment and at 3 months and 6 months after treatment were compared between the two groups.Results Before treatment,there were no significant statistical differences between the two groups（P>0.05）.At 3 months and 6 months after treatment,hypersensitive C reaction protein（Hs-CRP）,serum creatinine（SCr）,collagen type Ⅳ（Col-Ⅳ） and transformation growth factor（TGF-β） for the patients in the treatment group were all lower than those in the control group,with statistical significance of differences（P<0.05）.The levels of eGFR for the patients in the treatment group were also all lower than those in the control group,with statistical significance of differences（P<0.05）.Conclusions Clinical observations demonstrate that Shen’an pills can destroy the malignant cycle of "deficiency,dampness,stasis and poison",regulate water metabolism,promote blood circulation so as to remove blood stasis,and reduce toxins in the body,improving patients’ symptoms.At the same time,the ingredient rhubarb contained in Shen’an pills can postpone renal fibrosis,by inhibiting cell proliferation,inhibiting production of fibrogenic factors and regulating synthesis and decomposition of extracellular matrix.